52.9k views
0 votes
Gisele solved the quadratic equation x2 + 5x - 6 = 0 by factoring.

Her work is shown below.
Step 1: 22 +52 - 6 = 0
Step 2: (x + 2)(x + 3) = 0
Step 3: 2+2 = 0, 2+3 = 0
Step 4: E= -2 or 2= -3
Step 5: {-2, -3}
Gisele plugged her solutions into the original equation, and found that they did not work.
In which step did she first make a mistake?

2 Answers

2 votes

Answer:

step 1 .

Explanation:

User SmasherHell
by
4.6k points
3 votes

For this case we have the following quadratic equation:


x ^ 2 + 5x-6 = 0

To factorize, we must find two numbers that when multiplied result in -6 and when added together result in +5. These numbers are: -1 and +6


-1 + 6 = 5\\-1 * 6 = -6

Then we factor:


(x-1) (x + 6) = 0

Thus, the roots are:


x_ {1} = 1\\x_ {2} = - 6

So, Gisele was wrong in step 2. She couldn't find the correct values to factorize.

Answer:

Gisele was wrong in step 2. She couldn't find the correct values to factorize.

User Javier Perez
by
4.9k points